Interactive sensor-based balance training in older cancer patients with chemotherapy-induced peripheral neuropathy: a randomized controlled trial - Schwenk, Michael (Gerontology, 2016)
BACKGROUND: Cancer patients with chemotherapy-induced peripheral neuropathy (CIPN) have deficits in sensory and motor skills leading to inappropriate proprioceptive feedback, impaired postural control, and fall risk. Balance training programs specifically developed for CIPN patients are lacking.